Psikoz Olgularina Tedavi Uyumuna Yonelik Bir Terapi Programi Uygulanmasi - Ece Yazla; Mehmet Emrah Karadere; Halil Ibrahim Olcum (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Treatment adherence therapy is defined as implicit treatment efficacy and motivation of medication in the literature. It is a patient centered attempt which aims at increasing medical treatment compliance. It is applied by individual therapy sessions. It makes for a number of complex factors that affect treatment compliance. It utilizes psychoeducation together with motivational and cognitive behavioral approaches which regulate the beliefs of patients for treatment. This study was performed to investigate the effect of Treatment Adherence Therapy on treatment compliance of patients with psychosis. In the study, 26 patients took place in the case group while 24 patients were included in the control group. Brief Psychiatric Rating Scale and Medication Adherence Rating Scale were used. There was no statistically significant difference between the groups in terms of age and gender. Treatment Adherence Therapy Program was found to have a beneficial effect on disease symptoms and treatment compliance in the short term. It was determined that this effect had been decreased in the long term. This finding shows that the Treatment Adherence Therapy Program contributes to improvement of treatment compliance in psychotic cases. According to the results of the research it may be suggested that the therapy program should be repeated within 6 months at the latest. [JCBPR 2019; 8(2.000): 94-99]